Programming With Visual Basic.NET - Coombs, Ted
Learn to make the transition from Visual Basic 6 to Visual Basic.NET with this new book by best selling computer programming author Ted Coombs. The book is also suitable for programmers who want to learn Visual Basic.NET for the first time